Lactose-Functionalized Carbosilane Glycodendrimers Are Highly Potent Multivalent Ligands for Galectin-9 Binding: Increased Glycan Affinity to Galectins Correlates with Aggregation Behavior - Müllerová, Monika; Hovorková, Michaela; Závodná, Táňa; Červenková Št Astná, Lucie; Krupková, Alena; Hamala, Vojtěch; Nováková, Kateřina; Topinka, Jan; Bojarová, Pavla; Strašák, Tomáš (Biomacromolecules, 2023)
Galectins, the glycan binding proteins, and their respective carbohydrate ligands represent a unique fundamental regulatory network modulating a plethora of biological processes. The advances in galectin-targeted therapy must be based on a deep understanding of the mechanism of ligand-protein recognition. Carbosilane dendrimers, the well-defined and finely tunable nanoscaffolds with low toxicity, are promising for multivalent carbohydrate ligand presentation to target galectin receptors. The study discloses a synthetic method for two types of lactose-functionalized carbosilane glycodendrimers (Lac-CS-DDMs). Furthermore, we report their outstanding, dendritic effect-driven affinity to tandem-type galectins, especially Gal-9. In the enzyme-linked immunosorbent assay, the affinity of the third-generation multivalent dendritic ligand bearing 32 lactose units to Gal-9 reached nanomolar values (IC50 = 970 nM), being a 1400-fold more effective inhibitor than monovalent lactose for this protein. This demonstrates a game-changing impact of multivalent presentation on the inhibitory effect of a ligand as simple as lactose. Moreover, using DLS hydrodynamic diameter measurements, we correlated the increased affinity of the glycodendrimer ligands to Gal-3 and Gal-8 but especially to Gal-9 with the formation of relatively uniform and stable galectin/Lac-CS-DDM aggregates.
Keywords: vazba proteinů; Ligands; polysacharidy; galektiny; Lactose; Galectins; laktosa; Protein Binding; ligandy; Polysaccharides